Weakest Bus detection using CPF analysis in Power System - Sarkar, Dipu; Odyuo, Yanrenthung (International Journal of Computer Sciences and Engineering, 2025)
With the increase in the consumption and demand of electrical energy, it has been observed that there is a great strain on the central power grid to provide the required power without compromising its security. Thus, other mode of safe and secure power transmission to the consumers, with less strain to the grid is the need of the hour. This paper is focused on the CPF analysis of a power network. We have considered the IEEE 30-Bus benchmark system for our study and have obtained the load flow characteristics based on CPF method. All the simulations are carried out using the Power System Analysis Toolbox (PSAT).